ANALISIS PERUBAHAN PENGGUNAAN LAHAN RUANG TERBUKA HIJAU DI JAKARTA TIMUR - Santun R.P. Sitorus; Sukapti Ivanna Devi Patria; Dyah R. Panuju (Jurnal Lanskap Indonesia, 2012)
City development in Indonesia, especially in East Jakarta has affected the changing of land use. The increasing of physical building at the city has positively affected to the increasing economic activities. Besides, it has caused environmental degradation. One form of environmental degradation is decreasing of green open space which is turning into built-up area. This research aims: to identify the pattern of green open space change, to know the population growth’s rate and regional development in East Jakar-ta, and to assess factors affecting the green open space change. The result showed that in 2002, the green open space in East Jakarta was 830,6 ha and in 2007 it increased into 1.056,7 ha. Between the period of 2002 and 2007 there was an increasing about 226,1 ha. Population growth’s rate from 2002 until 2008 in East Jakarta was 0.9% per year, and inmigrant growth’s rate in the same period was 0.7% per year. The re-gional development was showed by the appearance of developed facilities including education, health and economic facilities. Growth rate of education, health and eco-nomic facilities in the period of 2003 and 2006 are -1.5%, 6.4% and 1.1 per year, re-spectively. Based on scalogram analysis, most of the kelurahan (town villages) in East Jakarta are belong to hierarchy III. In 2003, there were 40 kelurahan classified as hier-arcy III, 18 kelurahan as hierarchy II, and 7 kelurahan as hierarchy I. In 2006, the number of kelurahan grouped as hierarchy III decreased into 35 kelurahan, while at hierarchy II and I increased into 19 and 11 kelurahan, respectively. The most affecting factors (p-level ≤ 0.05) to the green open space change are availability of unoccupied area. Meanwhile, the potential affecting factor (p-level ≤ 0.1) to the green open space change is the increasing number of health facilities.Keywords: Area Development, Availability of Empty Area, Citizen Growth, Green Open Space